Study of Genus Bacillus (B. clausii) Probiotic Bacteria Regarding the Biogenic Extracellular Synthesis of Selenium Nanoparticles - Tymoshok, N.O.; Demchenko, O.A.; Kharchuk, M.S.; Bityutskyy, V.S.; Tsekhmistrenko, O.S.; Tsekhmistrenko, S.I.; Тимошок, Н.О.; Демченко, О.А.; Харчук, M.С.; Бітюцький, В.С.; Цехмістренко, О.C.; Цехмістренко, С.І. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
The biogenic method of nanoparticle synthesis with the participation of microorganisms that are capable of producing nanomaterials of different shapes, sizes, and chemical compositions is a promising innovative direction of nanotechnology. Bacteria are chosen for the production of nanoparticles due to their rapid reproduction, ease of cultivation, low energy requirements, and minimal costs. The complex synthetic mechanisms available to microorganisms allow them to use a large number of building blocks to construct new biosynthetic nanostructures that can accumulate in vesicles inside the cell or by extracellular synthesis. In the modern world, the so-called "green" technologies come to the fore, and the active studies of microorganisms with a high enzymatic potential, which can be used in nanobiotechnology and are promising for practical application, are being actively expanded. We have screened strains of Bacillus bacteria for their ability to reduce Se (IV) in the composition of sodium selenite to Se0. The aim of the research was to study the processes of biogenic synthesis of selenium nanoparticles by probiotic strains of Bacillus clausii and their prospects for practical application. Methods. Cultivation of B. clausii was carried out in vials (500 cm3) on a rotary shaker (20 rpm) at of 30 oC for 3 days on a nutrient medium of MPB. Sodium selenite 0.0065 g/100 mL was additionally added to the medium. A visual assessment of the color change in the nutrient culture medium was carried out under the conditions of its enrichment with 30 ppm Se in the composition of sodium selenite. The characteristics of nano-Se were studied using transmission electron microscopy (TEM). Results. It was established that the addition of sodium selenite 0.0065 g/100 mL (30 ppm Se) within the composition of sodium selenite to the nutrient medium revealed the ability of B. clausii to reduce oxyanions Se (IV) into nanoparticles of elemental selenium Se0 (appearance of orange color). Bacterial cells and biosynthesized selenium nanoparticles were separated for further transmission microscopy. Synthesized Nano-Se nanocrystals were detected in TEM images. Nano-Se particle sizes determined from TEM images varied within 298±52 nm. Nanoparticles obtained by B. clausii formed conglomerates of nanocrystals; individual nanoparticles had a spherical shape. A change in the color of the environment under the influence of Na2SeO3 during the cultivation of B. clausii was noted when the growth phase of the cultures went from logarithmic to stationary mode. Research has established for the first time that B. clausii is capable of reducing selenite to elemental selenium, as evidenced by TEM data. Conclusions. The obtained data indicate the ability of B. clausii to reduce sodium selenite with the formation of extracellular selenium nanoparticles (Nano-Se). The B. clausii-assisted transformation of sodium selenite with extracellular deposits of Nano-Se opens an accessible source of biogenic Nano-Se and the creation of selenium-containing probiotic preparations based on it.